Autobiography, Time, and Documentation in the Performances and Auto-Archives of Carolee Schneemann. (1st October 2016) - Barratt, Martha
Abstract : This article considers the archives of the American artist Carolee Schneemann (b. 1939), now held between Stanford University and the Getty Research Institute, Los Angeles, as a constitutive element of her performance practice. Analysis of items from these remarkable archives, such as sketchbooks, letters, and Life Books, in relation to her artistic output proper, aims to establish her critical attitude towards the structure of the traditional archive. Schneemann's documentation of her performance work through film and photography, and her re-use of such documentation in later projects, prompts further investigation into how time is structured in her work and restructured in its afterlife. The possible political implications of these tactics are then explored; the construction of self-image through autobiographical work, in tandem with her auto-archival practice, presents a feminist mode of inheritance in opposition to the logic of the traditional archive and the masculinist subject it presumes.